1-(6-O-Acetyl-3,4-Dideoxy-3-Fluoro-β-D-Glycero-Hex-3-enopyranosyl-2- Ulose)-N4-Benzoyl Cytosine is a potent inhibitor of pseudorabies virus replication in infected cells: 1-(6-O-Acetil-3,4-Dideoksi-3-Fluoro-β-D-Glicero-Hex-3-enopiranozil-2- Uloza)-N4-Benzoil Citozin je močan inhibitor replikacije pseudorabies virusa v okuženih celicah - Tanja , Botić; Manta, Stella; Komiotis, Dimitri; Lefevre, Francois; Cencič, Avrelija (Acta Medico-Biotechnica, 2021)
Purpose: We have previously shown that newly synthesized fluoro-glucopyranosyl derivatives of ketonucleosides represent a group of antiviral drugs potent against RNA viruses. The aim of the present study was to ascertain whether these compounds are equally efficient in combating DNA viruses in comparison with the commercially available drug ganciclovir.Methods: As a study model, the pseudorabies virus (NIA3 strain) and pig kidney cells (PK-15) were used.Results: Our results indicated that 1-(6-O-acetyl-3,4-dideoxy-3-fluoro-β-D-glycero-hex-3-enopyranosyl-2-ulose)-N4-benzoyl cytosine (compound 2) is a potent inhibitor of pseudorabies replication, with higher antiviral activity than was found for ganciclovir.Conclusion: Compound 2 has strong antiviral activity against the DNA virus pseudorabies.